The Effect of Schotel Corn Supplementary Feeding on Body Weight in Wasted and Severely Wasted - Ayu Pratamasari; Siti Chunaeni; Munayarokh Munayarokh (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
The incidence of malnutrition in toddler requires special attention because nutritional problems that occur since toddlers will have an impact on the further development of toddler life. Nutrition improvement is one way to overcome severely wasted and wasted. One of the efforts to increase toddler's weight is to provide supplementary feeding that is rich in nutrients such as corn. The nutritional content of sweet corn includes carbohydrates, fats, proteins, and some vitamins and minerals. Corn can be used for daily needs as a easy to modify food in various forms supplementary feeding such as schotle corn. The aim of this study was to knowing the effectiveness of corn schotle on body weight in toddlers aged 12-24 months at the Puskesmas Kebumen I. The type of research used is quantitative by used desain pre-experiment one group pretest-post test designe. The number of samples was 38 toddlers aged 12-24 months by means of total sampling. The results showed that before being given schotle corn to toddlers aged 12-24 months the median weight was 8.05 kg and after being given schotle corn the median weight increased to 8.15 kg. After going through the nonparametric Wilcoxon test, the p value = 0.000 (p value 0.05), this shows the provision of corn schotle this shows that giving schotle corn is effective for weight gain in toddlers aged 12-24 months.